Analisis Pencabutan Keterangan Terdakwa Dalam Berita Acara Pemeriksaan (BAP) Penyidikan Di Persidangan Terhadap Putusan Hakim - Sarimonang B Sinaga; Syafruddin Kalo; Muhammad Hamdan; Marlina Marlina (Universitas Sumatera Utara, 2019)
Abstract. The revocation information of the defendant in the news of the proceedings (BAP) investigation at the trial which is not accompanied by a fundamental and logical reason then the legal position of the description of the defendant in the BAP the investigation can be